Stranded assets: How policy uncertainty affects capital, growth, and the environment - Lucas Bretschger; Susanne Soretz (ETH Zurich, CER-ETH - Center of Economic Research, 2018)
Standard environmental economics prescribes policies which are optimal and implemented immediately. The paper argues that, in reality, environmental policy often deviates from the optimum and implementation is not deterministic but subject to major uncertainty and frequent change. We present a model with a stochastic policy process that affects investors' decisions and the composition of capital. We assume that pollution is reduced by private green services and public abatement. The government subsidizes green services and taxes dirty capital albeit at a rate which may become random, causing unexpected capital write-offs. Tax jumps depend on environmental degradation and the share of green services. We show how policy uncertainty affects capital valuation and how it alters individual portfolios, green services, and economic growth.
Keywords: Q52; Q54; O10; 330; Policy uncertainty; stranded assets; private abatement; stochastic growth